Treatment preferences and current practices regarding open tibial shaft fractures - Qian, Shengjun; Shen, Yechao; Sun, Lingling; Wang, Zhan (Frontiers in Public Health, 2024)
Purpose: The purpose of this study was to reveal the treatment preferences and current practices regarding open tibial shaft fracture (OTSF). Patients and Methods: Online surveys of treatment preferences and current practice of OTSF were conducted by orthopedic trauma doctors from various medical institutions in Zhejiang Province. The survey contains three modules. The first module is the basic information of the participants, the second module is the treatment patterns for Gustilo-Anderson type I-II (GA I/II), and the third module is the treatment patterns for Gustilo-Anderson type IIIA (GA IIIA). Furthermore, each treatment pattern was divided into four aspects, including antibiotic prophylaxis, irrigation and debridement, fracture stabilization, and wound management. Results: A total of 132 orthopedic trauma doctors from 41 hospitals in Zhejiang province, participated the online surveys. In GA Ⅰ-IIIA OTSF, more than three-quarters of participants considered ＜3 hours as the appropriate timing of antibiotic administration after trauma. In fact, only 41.67% of participants administered antibiotics within 3 hours after trauma. 90.91% and 86.36% of participants thought debridement within 6 hours was reasonable for GA I/II and GA IIIA OTSF, respectively. However, in reality only about half of patients received debridement within 6 hours on average. The most common reason for delayed debridement was patients’ transport delay. 87.88% and 97.3% of participants preferred secondary internal fixation following external fixation for GA I/II and GA IIIA OTSF, respectively. Additionally, over half of participants preferred use of locking plate for treating GA I-IIIA OTSF. The most common reasons for choosing delayed internal fixation for GA I-IIIA OTSF were infection risk and damage control. 78.79% and 65.91% supported immediate internal fixation after removing the external fixation for GA I-IIIA OTSF, respectively. Regarding wound closure, 86.36% and 63.64% of participants reported primary closure for GA I/II and GA IIIA OTSF, respectively. Over three fourths of participants agreed that preoperative and postoperative multiple wound cultures should be performed to predict infection for GA I-IIIA OTSF. Conclusion: The study first presents the preference and practice regarding management of GA I-IIIA OTSF in Zhejiang, which may provide a reference for orthopedic surgeons.